Pelops: The Emergence of a Mythical Personality From Folktale, Ritual and Geography - Patay-Horváth, András (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Heroes were generally imagined by the ancient Greeks as historical personalities from a distant past who were remembered even centuries later and whose deeds became legendary. Although this concept is occasionally found even today, it is much more probable and indeed it is generally agreed that mythical heroes were not created in this way, but myths somehow evolved from/in tandem with rituals and/or as aetiological tales. On the other hand, the close connections between folktales and myths were always acknowledged, even if the nature of their relationship remains controversial. In this paper, the mythical biography of Pelops is discussed because I think it offers an instructive case-study illustrating the complexities involved. All the episodes of Pelops’ myths follow distinct folktale patterns and each of them was most probably inspired by different factors such as geography (strange rock formations around Mount Sipylos), popular etymology (the name of the Peloponnese) and ritual (some special cult practices in early Iron Age Olympia). The episodes of the hero’s life (childhood, marriage, kingship) were only loosely connected to each other and they were not amalgamated into a coherent biography until the end of the 19th century.